Relationship between subjective well-being and self-care among caregivers in pandemic times - Ogassavara, Dante; Ferreira de Souza, Juliana; Fuga da Silva, Daiane; Bartholomeu, Daniel; Montiel, José Maria (O Mundo da Saúde, 2022)
Self-care refers to disease prevention and health maintenance practices. Self-care capacity can be an important factor in different conditions and contexts and when associated with aspects of an individual’s health it can provide direct benefits to this person. During the Pandemic (COVID-19) this ability may be diminished or impaired, and even hindered with affective aspects, influencing their subjective well-being, that is, affecting their assessment of their own well-being. Thus, this study aimed to evaluate the relationship between self-care capacity and the affective attribution (positive or negative) of male and female adults who act as caregivers. The instruments used were a sociodemographic questionnaire, the Positive and Negative Affect Schedule and the Scale to Assess Self-Care Capabilities. After analyzing the frequency of the variables, Pearson’s correlation analysis was performed and through it, moderate associations (medium high) were revealed between the measure of positive affect and self-care (r=0.62; p=0.000) and negative affect and self-care, in this case, with a negative coefficient (r=-0.42; p=0.000); thus, this indicates that people tend to have more self-care, have better positive affects and less negative affects, respectively. It was possible to infer the idea that well-being and quality of life are intertwined with the affective attribution of the individual.